2019
DOI: 10.4062/biomolther.2019.005
|View full text |Cite
|
Sign up to set email alerts
|

S1P1 Regulates M1/M2 Polarization toward Brain Injury after Transient Focal Cerebral Ischemia

Abstract: M1/M2 polarization of immune cells including microglia has been well characterized. It mediates detrimental or beneficial roles in neuroinflammatory disorders including cerebral ischemia. We have previously found that sphingosine 1-phospate receptor subtype 1 (S1P1) in post-ischemic brain following transient middle cerebral artery occlusion (tMCAO) can trigger microglial activation, leading to brain damage. Although the link between S1P1 and microglial activation as a pathogenesis in cerebral ischemia had been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 46 publications
0
27
0
Order By: Relevance
“…In opposition to S1P 2 , pathogenic mechanisms of S1P 1 and S1P 3 in cerebral ischemia rely on microglial activation [239,240]. Moreover, the same group elucidated the importance of S1P 1 -regulation in promoting a pro-inflammatory M1 polarization of astrocytes, which was brought about by the intracellular signal transducers ERK1/2, p38, and JNK MAPK favoring brain damage after cerebral ischemia [241]. Furthermore, Zamanian et al, examined reactive astrogliosis in response to either MCAO or LPS and showed Pentraxin-related protein PTX3 (PTX3), tumor necrosis factor receptor superfamily member 12A (TNFRSF12A), and S1P 3 to be markers of reactive astrocytes after MCAO [242].…”
Section: The Sphingolipid Metabolism In Cerebrovascular Diseasesmentioning
confidence: 99%
“…In opposition to S1P 2 , pathogenic mechanisms of S1P 1 and S1P 3 in cerebral ischemia rely on microglial activation [239,240]. Moreover, the same group elucidated the importance of S1P 1 -regulation in promoting a pro-inflammatory M1 polarization of astrocytes, which was brought about by the intracellular signal transducers ERK1/2, p38, and JNK MAPK favoring brain damage after cerebral ischemia [241]. Furthermore, Zamanian et al, examined reactive astrogliosis in response to either MCAO or LPS and showed Pentraxin-related protein PTX3 (PTX3), tumor necrosis factor receptor superfamily member 12A (TNFRSF12A), and S1P 3 to be markers of reactive astrocytes after MCAO [242].…”
Section: The Sphingolipid Metabolism In Cerebrovascular Diseasesmentioning
confidence: 99%
“…Specifically, S1P1 activation influences mitogen-activated protein kinases and phosphoinositide 3-kinase/Akt activation in the ischemic hemisphere, and those pathways can increase M1 polarization while simultaneously decreasing M2 polarization. The influence is especially significant on microglia M1 polarization (122). These results may lead to further study of S1P subtypes on their relationships with and regulation of the M1/M2 polarization of microglia.…”
Section: Resident Glial Cells and Infiltrating Macrophages/monocytesmentioning
confidence: 99%
“…The effect of kellerin on the NLRP3 signaling pathway may be responsible for its function in regulating microglial polarization. MAPK signaling pathways also mediate microglial polarization during cerebral ischemia (Gaire, Bae, & Choi, ; Gaire, Song, & Choi, ; Xiang et al, ). MAPKs function as three‐tiered kinase cascades leading to the activation of the effector kinases ERK, p38, and JNK (Kondreddy et al, ; Lanna et al, ).…”
Section: Discussionmentioning
confidence: 99%